Intestinal Fluid Permeability in Atlantic Salmon (Salmo salar L.) Is Affected by Dietary Protein Source. - Haibin Hu; Trond M Kortner; Karina Gajardo; Elvis Chikwati; John Tinsley; Åshild Krogdahl (PLoS ONE, 2016)
In Atlantic salmon (Salmo salar L.), and also in other fish species, certain plant protein ingredients can increase fecal water content creating a diarrhea-like condition which may impair gut function and reduce fish growth. The present study aimed to strengthen understanding of the underlying mechanisms by observing effects of various alternative plant protein sources when replacing fish meal on expression of genes encoding proteins playing key roles in regulation of water transport across the mucosa of the distal intestine (DI). A 48-day feeding trial was conducted with five diets: A reference diet (FM) in which fish meal (72%) was the only protein source; Diet SBMWG with a mix of soybean meal (30%) and wheat gluten (22%); Diet SPCPM with a mix of soy protein concentrate (30%) and poultry meal (6%); Diet GMWG with guar meal (30%) and wheat gluten (14.5%); Diet PM with 58% poultry meal. Compared to fish fed the FM reference diet, fish fed the soybean meal containing diet (SBMWG) showed signs of enteritis in the DI, increased fecal water content of DI chyme and higher plasma osmolality. Altered DI expression of a battery of genes encoding aquaporins, ion transporters, tight junction and adherens junction proteins suggested reduced transcellular transport of water as well as a tightening of the junction barrier in fish fed the SBMWG diet, which may explain the observed higher fecal water content and plasma osmolality. DI structure was not altered for fish fed the other experimental diets but alterations in target gene expression and fecal water content were observed, indicating that alterations in water transport components may take place without clear effects on intestinal structure.